Pengembangan Lembar Kerja Peserta Didik (LKPD) Materi Bentuk Aljabar Berbasis Literasi Dalam Pembelajaran Daring Terhadap Kemandirian Belajar Siswa - Syahfitri Pratiwi, Dhyta (Lembaga Riset Mutiara Akbar, 2022)
In research on the development of literacy-based student worksheets, it aims to find out/see the quality/quality of student worksheets as teaching materials/learning media. The type of research used is the ADDIE development model, namely analysis, design, development, implementation and evaluation. However, this research is limited to the third stage, namely the development stage. This research activity was conducted at MTs Al-Azhar Bulu Cina school. The research instrument used was a validity questionnaire, the practical sheet of the subject teacher's response questionnaire that was given aimed at seeing the results of the developed student worksheets and the questionnaire used to see student responses aimed at seeing student responses to the developed teaching materials. The results of data analysis in product development are 3, namely: The results of the validation of the literacy-based LKPD were assessed by two mathematicians who produced a total score of 163 with a very valid category in product development, The results of the assessment sheet conducted by the teacher obtained a total score of 39 with a very category Practically, the results of the assessment of student responses with the number of participants as many as 25 people to the literacy-based LKPD developed obtained a percentage of 80% with a strong category. Student worksheets/teaching materials designed/developed using this research obtained good quality products and for learning media/teaching materials in schools